Dynamics of civil structures. proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics, 2016 /: proceedings of the 34th IMAC, a Conference and Exposition on Structural Dynamics, 2016. Volume 2 : (2016) - Unknown
No abstract available